An Array of M-Shaped Vivaldi Antennas for UWB Applications - Omar, Shokhan A.; Iqbal, Amjad; Saraereh, Omar A.; Basir, Abdul (E M W Publishing, 2017)
In this paper, a novel M-shaped UWB Vivaldi array antenna is presented. First of all, a simple M-shaped UWB Vivaldi antenna is designed, and its properties of return loss, radiation pattern, VSWR, gain, etc. are analyzed. An array of M-shaped UWB antenna is simulated and designed after the successful implementation of the simple UWB Vivaldi antenna. The designed antenna has operating frequency from 3.25 GHz to 8.85 GHz covering 5.6 GHz bandwidth. The antenna has flat gain over entire frequency range. The proposed antenna is fabricated on a commercially available FR-4 substrate having relative permittivity of 4.4 and height of 1 mm. The proposed antenna has wide band and good flat gain over entire frequency range. The proposed antenna can be used in next generation wireless communication because of its efficiency, gain and wide bandwidth.
Keywords: Monopolar Antenna; Band; Design